HARMFUL ENTOMOCOMPLEX OF THE APPLE ORCHARD - Holiachuk , Ю.; Kosylovych , Г.; Hulko , Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The apple tree is the main fruit crop cultivated in Ukraine. Despite the gradual reduction in the area of fruit-bearing apple orchards, the gross yield of apples is increasing due to the rising productivity of the crop. This is facilitated by modern apple cultivation technologies. However, orchard plantations create a favorable environment for the development of harmful organisms due to the long-term monoculture cultivation of apple trees. To reduce pest-related losses, integrated pest management systems are used, with phytosanitary monitoring of orchard conditions serving as their foundation. The aim of this research was to determine the species composition of pests in fruit-bearing apple orchards at the Educational and Scientific Centre of Lviv National Environmental University in 2023–2024. Monitoring results revealed a predominance of insect pests from the orders Homoptera and Lepidoptera. During the budburst stage, adult apple blossom weevils, bud weevils, and apple leaf cutters caused damage to the apple orchard. During the flowering phase, the most harmful pest was the apple blossom weevil, whose larvae destroyed bud contents, leading to direct crop losses. During the fruit development stage, aphids were the most numerous, especially the green apple aphid, whose infestation levels in 2024 reached up to 85% of young shoots of some trees. The woolly apple aphid also became widespread, with colonies found even on the surface and inside the fruits. Among the leaf-chewing Lepidoptera, the most widespread species was the grey fruit-tree case moth. Among carpophagous pests, the apple fruit sawfly and codling moth were detected, although the infestation of apple fruits by their larvae was insignificant.